The Development of Learning Skills in Inclusive Education Classroom of Exceptional and Ordinary Students Majoring in General Science, and Early Childhood, Faculty of Education, Kalasin University - อินทรสุขสันติ, รัชดาพรรณ; รัตนธารทอง, เยาวเรศ; มหาอุตร, ศักดิ์ชัย; ผลดี, ภัทรพร (Journal of Roi Et Rajabhat University, 2016)
The purposes of this research were to study 1) the process of classroom management development of exceptional and ordinary students, 2) the skills of inclusive classroom management for exceptional and ordinary students and 3) the students’satisfaction towards the development of inclusive classroom management of exceptional and ordinary students. The total sample was 97 students majoring in Science and Early Childhood Education from the Faculty of Education, Kalasin University using purposive sampling technique. The research instruments were pre–test and post–test, three different exercises of individual lesson plans, and interviews. Mean, frequency, and percentage were used for data analysis. The research results were as follows: 1) The learning process could be developed through Bloom’s Taxonomy consisting of Knowledge, Comprehension, Application, Analysis, Synthesis, and Evaluation. 2) The students’ scores from the post–test were higher than those from the pre–test. The students could create their individual lesson plans which received the highest scores in the third time of the experiment. 3) The level of students’ satisfaction towards classroom management development was at a high level. The students showed their high level of satisfaction rated from the highest to the lowest were the appropriate of content and time period in conducting learning activities, the positive attitudes towards exceptional and ordinary students after taking the inclusive education course and the application of inclusive education policy to their real life after graduation. The lowest level of students’ satisfaction was the teacher’s knowledge and skills in transferring in classroom management.